Evaluation of the Operational Modal Responses in Linear Switched Reluctance Actuators - Salvado, José A. (2020)
The vibrations produced by switched reluctance drives have been studied by numerous authors, mainly for those producing rotational movement. This paper deals with the problem of vibrations produced by linear switched reluctance actuators in operation. We propose a test setup to measure and evaluate the operational responses produced by linear switched reluctance actuators. The phase current and the local accelerations are presented and analyzed, and its frequency components are evaluated and discussed concerning the natural modes obtained from a study supported by finite elements analysis. The information about the operational modal responses is important to establish the control strategies and to avoid switching frequencies close to those of the natural modes.